2021
DOI: 10.3145/epi.2021.nov.02
|View full text |Cite
|
Sign up to set email alerts
|

When polarization hits corporations: the moderating effect of political ideology on corporate activism

Abstract: Traditionally, it has been argued that companies should maintain a neutral stance on issues of a social or political nature, especially controversial ones. However, in recent years, corporations have begun to adopt clear positions on sensitive and polarizing social and political issues. This new phenomenon, called corporate activism, is beginning to gain prominence in corporate strategies, which now extend beyond business objectives and sometimes may go against the beliefs held by many customers. To date, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
(87 reference statements)
0
2
0
2
Order By: Relevance
“…In summary, previous empirical literature has focused on the relationship between corporate activism and purchase intention (Corcoran et al, 2016;Krebel Chang, 2017;Overton et al, 2021;Robinson et al, 2012), changes in consumer attitudes (Atanga et al, 2022;Parcha & Kingsley Westerman, 2020), the impact on brand equity (Korschun et al, 2019;Vredenburg et al, 2020), reputation (Den-Hond et al, 2014), or both (Villagra, Clemente-Mediavilla, et al, 2021), as well as understanding the antecedents of the concept (institutional and corporate credibility and authenticity) from the consumer's point of view (Villagra et al, 2022). Moreover, the relationship between corporate activism and financial performance is receiving research attention (Bhagwat et al, 2020;Dodd, 2018;Dodd & Supa, 2014;Glambosky & Peterburgsky, 2022;Villagra, Monfort, & Méndez-Suárez, 2021;Weinzimmer & Esken, 2016), which is closely related to the principal objective of this research.…”
Section: Principles Of Corporate Activismmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, previous empirical literature has focused on the relationship between corporate activism and purchase intention (Corcoran et al, 2016;Krebel Chang, 2017;Overton et al, 2021;Robinson et al, 2012), changes in consumer attitudes (Atanga et al, 2022;Parcha & Kingsley Westerman, 2020), the impact on brand equity (Korschun et al, 2019;Vredenburg et al, 2020), reputation (Den-Hond et al, 2014), or both (Villagra, Clemente-Mediavilla, et al, 2021), as well as understanding the antecedents of the concept (institutional and corporate credibility and authenticity) from the consumer's point of view (Villagra et al, 2022). Moreover, the relationship between corporate activism and financial performance is receiving research attention (Bhagwat et al, 2020;Dodd, 2018;Dodd & Supa, 2014;Glambosky & Peterburgsky, 2022;Villagra, Monfort, & Méndez-Suárez, 2021;Weinzimmer & Esken, 2016), which is closely related to the principal objective of this research.…”
Section: Principles Of Corporate Activismmentioning
confidence: 99%
“…They also found that the higher the perceived credibility and authenticity of companies, the more positively their corporate activism actions will be regarded. In addition, Villagra, Clemente-Mediavilla, et al (2021) found that consumers' political ideology could act as a moderating variable of the effects of corporate activism. On the one hand, consumers with a more conservative ideology do not consider that the activist actions of companies will have positive consequences on their reputation and brand value.…”
Section: The Relationship Between Corporate Activism and Firm Perform...mentioning
confidence: 99%
“…Como se ha observado en los apartados previos, el activismo corporativo, de gran interés y desarrollo en los últimos años, ha sido estudiado desde perspectivas diversas. Sin embargo, no hay apenas estudios que se centren en explicar si es aceptado o no por los públicos de las organizaciones (Mukherjee y Althuizen, 2020;Parcha y Kingsley, 2020;Villagra et al, 2021b). No obstante, es interesante profundizar en teorías previas que, aún sin tener una relación directa con el tema, pueden servir como punto de partida para explicar los comportamientos y situaciones desde el punto de vista de la compañía y sus públicos.…”
Section: Conclusiones E Implicacionesunclassified
“…Este modelo puede aplicarse a diferentes stakeholders, esto es, consumidores con características sociodemográficas muy diversas (edad, país de origen, situación económica, etc. ), distintas ideologías políticas (Mukherjee y Althuizen, 2020;Villagra et al, 2021b), inversores de varios sectores (Bhagwat et al, 2020, Sánchez et al, 2022 u otros a considerar por futuros autores.…”
Section: Conclusiones E Implicacionesunclassified